Value Chain Marketing A Marketing Strategy to Overcome Immediate Customer Innovation Resistance - Hintze, Stephanie; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
Value Chain Marketing (VCM) is a promising strategy to overcome immediate customers$1 (Binnovation resistance. By pursuing VCM, material suppliers enlarge their target group beyond their immediate customers and address their downstream customers as well. Treading on relatively unexplored grounds, this book explores the relevance of VCM and comprehends its process; identifies the critical factors for suppliers$1 (Bmarketing success, and compares the performance of VCM trials, using a multi-method design linking case study research and computational modeling.s
Focus and Scope: Introduction -- Conceptual and Methodological Foundation: Dealing with Value Chains -- Marketing Supplier Innovations -- Research Design and Methodology -- Qualitative Studies: Pilot Study -- Case Study -- Computational Modeling: Agent-Based Simulation Study -- Integrating Findings: Discussion of Findings -- Conclusions -- Appendix: Details - Pilot Study -- Details - Case Study -- Details - Agent-Based Simulation Study.
Keywords: Business; Marketing; Management; Industrial management; Computer simulation; Business and Management; Marketing; Innovation/Technology Management; Simulation and Modeling; Electronic books